(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The problem of man’s will today stands at the center of political and spiritual life, which is determined by the level of achievement of modern society, its democratic culture is the main criterion of civilization. The will and predestination are the conditions of existence of the individual. When people determine the objectives of their actions, they acquire a free. The destiny of man is not an absolute concept, mysterious and special. Interest in the fate to the will for freedom and mystery attract the attention of anyone. At least once in his life every person thinks of a question - whether the person is really free in his behavior and it all depends on his fate. The purpose of this article to reveal versatile, philosophical, psychological, literary and religious positions problem of will and predestination. Key words: God, conscience, will, destiny, freedom, debt